Economic and performance evaluation of electrocoagulation unit for the treatment of hexavalent chromium using Taguchi method - Kumar, A.; Basu, D. (International journal of environmental science and technology (Tehran), 2023)
In this study, a batch-scale electrocoagulation (EC) reactor with fixed aluminium electrodes was examined, for the removal of hexavalent chromium [Cr(VI)] from synthetic wastewater. The effects of operating parameters namely current density, initial Cr(VI) concentration and initial pH on the performance of the EC process were established. Taguchi method (L 9 orthogonal array (OA) with 3-factors in 3-levels) was used to obtain the optimum working condition for the operating parameters for maximum Cr(VI) removal. The performance characteristics i.e. signal-to-noise (S–N) ratio (the larger-the-better) and analysis of variance (ANOVA) were considered to compare the relative greatness of a factor’s effect on the response parameter. The optimum working condition was obtained at initial Cr(VI) concentration: 15 mg/L; current density: 49.3 mA/cm 2 and initial pH: 5. Increase in current density led to enhanced Cr(VI) removal. On the contrary, the removal efficiency was inversely proportional to the initial Cr(VI) concentration. The applicability of the additive model was proven by the high R 2 value (0.998) and lower value (0.6068) of Root Mean Square Error (RMSE). The ANOVA results suggested that the current density, initial Cr(VI) concentration and initial pH had a notable influence on the Cr(VI) removal, with contributions of 2.35%, 78.68% and 18.91%, respectively. At the optimum condition, an X-ray fluorescence (XRF) analysis confirmed the presence of Al(OH) 3 and Cr(OH) 3 precipitate in the sludge sample, confirming the removal of Cr(VI). The total operational cost (OC) was calculated as $10.77/m 3 , at optimum conditions.